2018
DOI: 10.3382/ps/pex335
|View full text |Cite
|
Sign up to set email alerts
|

Carcass characteristics, meat quality, and fatty acid composition of wild-living mallards (Anas platyrhynchos L.)

Abstract: The aim of this study was to determine the carcass characteristics, meat quality, and fatty acid composition of wild-living mallards. The experimental materials comprised 30 mallards (1:1 sex ratio) harvested during the hunting season in northeastern Poland. The carcasses were transported to the laboratory where they were weighed individually, plucked, dressed, and dissected. The proximate chemical composition and physicochemical properties of meat and the fatty acid profile of breast muscle lipids were determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
13
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(44 citation statements)
references
References 21 publications
5
13
6
Order By: Relevance
“…The deposition of fatty acids in meat was a complex and dynamic process, that could be affected by various factors such as age, sex, breed and rearing conditions of the animals. In the current study, we identified 20 fatty acids in duck breast muscle and found that the species and predominance order of indicated fatty acids were similar to previous reports [14,27,28]. We compared the composition of fatty acid between male and female ducks and found that it was really difficult to make a clear conclusion about the influence of duck sex on fatty acid composition of breast muscle.…”
Section: Effect Of Age Sex and Breeds On The Accumulation Of Fatty Asupporting
confidence: 73%
See 2 more Smart Citations
“…The deposition of fatty acids in meat was a complex and dynamic process, that could be affected by various factors such as age, sex, breed and rearing conditions of the animals. In the current study, we identified 20 fatty acids in duck breast muscle and found that the species and predominance order of indicated fatty acids were similar to previous reports [14,27,28]. We compared the composition of fatty acid between male and female ducks and found that it was really difficult to make a clear conclusion about the influence of duck sex on fatty acid composition of breast muscle.…”
Section: Effect Of Age Sex and Breeds On The Accumulation Of Fatty Asupporting
confidence: 73%
“…It has been speculated in previous studies that the high levels of PUFAs (C20 and C22) in the meat of wild mallards mainly resulted from the birds' diet, as these fatty acids can be derived from exogenous sources [14,33]. In the present study, all the ducks were reared under the same conditions, suggesting that the different fatty acid profiles of the two breeds were mainly due to genetic variation between them.…”
Section: Effect Of Age Sex and Breeds On The Accumulation Of Fatty Amentioning
confidence: 59%
See 1 more Smart Citation
“…Damaziak et al (2014) noticed greater diameters of white and red fibres of the pectoralis major muscle in 10-wk-old female and 12-wk-old male Muscovy ducks compared to Pekin ducks aged 7 weeks, which is consistent with our findings. Witkiewicz et al (2004) found a significantly higher percentage of white fibres (αW) and diameters of red fibres (17.5 µm 2 ) and white fibres (33.1 µm 2 ) in the pectoralis major muscle of Pekin ducks from the A44 pedigree flock, which are improved for (Janiszewski et al 2018) with wild-living mallards (Anas platyrhynchos) showed significantly higher diameters of white fibres (36.15 µm 2 ) and red fibres (16.14 µm 2 ) in females than in males (33.91 and 15.35 µm 2 , respectively), but this was not confirmed by our findings. Our results may suggest the greatest effect of genotype on microstructural characteristics of pectoralis major muscle.…”
Section: Resultsmentioning
confidence: 99%
“…MBG and BH1 had a lower Ʃn−6/Ʃn−3 value but higher contents of PUFAs (n−3, n−6), which suggested that the breast muscle of MBG and BH1 might have better fatty acid composition. Other studies showed that the high content of MUFA could increase the palatability of meat, while SFA could increase the risk of cardiovascular diseases ( Janiszewski et al, 2018 ; Jiang et al, 2013 ; Temple, 2018 ). The C22:1(n−9) was one of the most abundant MUFA among 5 duck breeds/strains.…”
Section: Discussionmentioning
confidence: 99%